In vitro Evidence of Human Immune Responsiveness Shows the Improved Potential of a Recombinant BCG Strain for Bladder Cancer Treatment - Rodriguez, Dunia; Goulart, Cibelly; Pagliarone, Ana C.; Silva, Eliane P.; Cunegundes, Priscila S.; Nascimento, Ivan P.; Borra, Ricardo C.; Dias, Waldely O.; Tagliabue, Aldo; Boraschi, Diana; Leite, Luciana C. C. (Frontiers in Immunology, 2019)
The live attenuated mycobacterial strain BCG, in use as vaccine against tuberculosis, is considered the gold standard for primary therapy of carcinoma in situ of the bladder. Despite its limitations, to date it has not been surpassed by any other treatment. Our group has developed a recombinant BCG strain expressing the detoxified S1 pertussis toxin (rBCG-S1PT) that proved more effective than wild type BCG (WT-BCG) in increasing survival time in an experimental mouse model of bladder cancer, due to the well-known adjuvant properties of pertussis toxin. Here, we investigated the capacity of rBCG-S1PT to stimulate human immune responses, in comparison to WT-BCG, using an in vitro stimulation assay based on human whole blood cells that allows for a comprehensive evaluation of leukocyte activation. Blood leukocytes stimulated with rBCG-S1PT produced increased levels of IL-6, IL-8 and IL-10 as compared to WT-BCG, but comparable levels of IL-1, IL-2, IFN- and TNF-. Stimulation of blood cells with the recombinant BCG strain also enhanced the expression of CD25 and CD69 on human CD4+ T cells. PBMC stimulated with rBCG-S1PT induced higher cytotoxicity to MB49 bladder cancer cells than WT-BCG-stimulated PBMC. These results suggest that the rBCG-S1PT strain is able to activate an immune response in human leukocytes that is higher than that induced by WT-BCG for parameters linked to better prognosis in bladder cancer (regulation of immune and early inflammatory responses), while fully comparable to WT-BCG for classical inflammatory parameters. This establishes rBCG-S1PT as a new highly effective candidate as immunotherapeutic agent against bladder cancer.